UMWERTUNGEN IN LISZTS WASSER-MUSIK - Márta-Adrienne ELEKES (Studia Universitatis Babeş-Bolyai. Musica)
The magnificence of The fountains of Villa d'Este - which advanced the impressionist music - launched the idea to found out what were the antecedents and maybe the after life of the attitude toward this theme in the Liszt’s life works concerning the music written for piano. My main goal was not to analyze some works, because anyway it exist a large literature about. I’ve clung into this theme as to a connecting thread which would help me to discover what kind of content attitude could be observed among some works and what kind of musical toolbar was born in the composer’s workshop. To make it simple, what was the meaning or how it happened that this “watery” theme came into the light and in what formal solution was this concluded.